Science, Religion, and Human Identity: Contributions from the Science and Religion Forum - Lawson, Finley (Zygon, 2022)
The Science and Religion Forum promotes discussion on issues at the interface of science and religion. The forum membership is diverse including professionals, academics, clergy, and interested lay people and each year it holds a conference to encourage discussion and exploration of issues that arise at the interface of science and religion. This article provides an overview of the online conference that took place in May 2021 and introduces this thematic section that includes six articles from the conference.